The Intensification of the Caste Divide: Increasing Violence on the Dalits in Neoliberal India: La intensificación de la división por casta: el aumento de la violencia contra los dalits en la India neoliberal - Bhosale, Jyoti (Araucaria, 2025)
This paper is a study of the increasing instances of violence on the Dalits in contemporary India. It contextualises such violence in the new economic reforms of the 1990s which inaugurated the neo-liberal policies of privatisation and signified a withdrawal from a certain kind of state welfare. Apart from the extended role for the market, such a transition is also worked out by manoeuvring with the constitutional mandated form of social justice. By examining the physical, structural, and the symbolic infliction of violence on the Dalits, this paper argues that the caste divide has intensified.